2004
DOI: 10.1163/1568551042580154
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects in oil palm fiber reinforced phenol formaldehyde composites: Studies on thermal, biological, moisture and high energy radiation effects

Abstract: Accelerated weathering studies of untreated and treated oil palm fiber reinforced phenol formaldehyde composites and oil palm/glass hybrid fiber reinforced phenol formaldehyde composites were conducted. Thermal, water, biological and γ radiation effects on the composite properties were analysed. Mechanical properties such as tensile, flexural and impact properties of thermal and water aged samples were investigated. The extent of biodegradation and γ irradiation effects was estimated from variations in tensile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…The integration of variety of fibers in a single matrix results in the development of hybrid biocomposites. Reinforcements have been incorporated either by: (i) intermingling of two types of short fibers thoroughly before incorporating them into the polymer in a mixer, or added alternately into the polymer with or without modification [87][88][89]. (ii) sandwiching of fibers or their mats or fabrics [20,89] or (iii) using non-woven or woven fabrics of both types of reinforcements, as in the case of glass fiber-LC fiber composite systems [20,89,90].…”
Section: Hybrid Compositesmentioning
confidence: 99%
“…The integration of variety of fibers in a single matrix results in the development of hybrid biocomposites. Reinforcements have been incorporated either by: (i) intermingling of two types of short fibers thoroughly before incorporating them into the polymer in a mixer, or added alternately into the polymer with or without modification [87][88][89]. (ii) sandwiching of fibers or their mats or fabrics [20,89] or (iii) using non-woven or woven fabrics of both types of reinforcements, as in the case of glass fiber-LC fiber composite systems [20,89,90].…”
Section: Hybrid Compositesmentioning
confidence: 99%
“…Alrededor de 1,1 t de fibras generadas por cada tonelada de aceite producido, podrían ser utilizadas como materia prima para productos industriales y artesanales, en la fabricación de biocompuestos naturales, lo cual reduce la utilización de polímeros (Shinoj et al, 2011), obteniendo así mayor degradabilidad, menor toxicidad (Rozman et al, 2003), mejores propiedades mecánicas, resistencia térmica y al paso del agua (Sreekala et al, 2004), así como productos útiles en la industria de plastificantes y de accesorios para automóviles (Shuit et al, 2009).…”
Section: Biomasaunclassified
“…These oil palm empty fruit bunch consist of high cellulose content and is a potential natural fibre resources, but its applications account for a small percentage of the total biomass productions. High cellulose content and high toughness value of oil palm EFB fibres make it suitable for application in polymer composites (Sreekala et al, 2004;. The cell wall of OPF also consists of cellulose, hemicellulose and lignin.…”
Section: Chemical Composition Of Oil Palm Fibresmentioning
confidence: 99%
“…Results out put indicated that Hybridization of oil palm fibre with glass fibre considerably decreased the water sorption of oil palm composite. Accelerated weathering studies of untreated and treated oil palm/glass reinforced PF composites conducted and observed biodegradation and irradiation effects in light of variations in tensile and impact properties (Sreekala et al 2004). Results indicated that mechanical performance of hybrid composites decreased with thermal and radiation ageing.…”
Section: Oil Palm/glass Fibres Reinforced Hybrid Compositesmentioning
confidence: 99%